2020
DOI: 10.1101/2020.10.14.20212837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking SARS-CoV-2 RNA through the wastewater treatment process

Abstract: The municipal sewage carries the new coronavirus (SARS-CoV-2), shed by COVID-19 patients, to wastewater treatment plants. Proper wastewater treatment can provide an important barrier for preventing uncontrolled discharged of the virus into the environment. However, the role of the different wastewater treatment stages in reducing virus concentrations was, thus far, unknown. In this work, we quantified SARS-CoV-RNA in the raw sewage and along the main stages of the wastewater process from two different plants i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
3
0
3
Order By: Relevance
“…Ressalta-se que, embora relatos tenham indicado que as unidades secundárias de tratamento tenham sido capazes de remover e inativar parcelas significativas de vírus entéricos (YANG et al, 2020;, as unidades não têm sido capazes de remover de forma completa o SARS-CoV-2 em plantas de tratamento de águas residuais em escalas reais (MOHAN et al, 2021;SERRA-COMPTE et al, 2021). De acordo com estudos procedidos em ETEs na Espanha, Japão, Israel e Índia, fragmentos do genoma do SARS-CoV-2 ainda foram capazes de ser detectados em amostras de efluentes secundários (ALI et al, 2020;HARAMOTO et al, 2020;RANDAZZO et al, 2020;KUMAR et al, 2021). Embora os processos secundários relatados nos estudos tenham apresentado diferenças operacionais significativas, a implementação de unidades terciárias de tratamento foi fortemente recomendada com o intuito de reduzir a possibilidade de propagação do SARS-CoV-2 através das matrizes aquáticas.…”
Section: Processos Biológicosunclassified
See 2 more Smart Citations
“…Ressalta-se que, embora relatos tenham indicado que as unidades secundárias de tratamento tenham sido capazes de remover e inativar parcelas significativas de vírus entéricos (YANG et al, 2020;, as unidades não têm sido capazes de remover de forma completa o SARS-CoV-2 em plantas de tratamento de águas residuais em escalas reais (MOHAN et al, 2021;SERRA-COMPTE et al, 2021). De acordo com estudos procedidos em ETEs na Espanha, Japão, Israel e Índia, fragmentos do genoma do SARS-CoV-2 ainda foram capazes de ser detectados em amostras de efluentes secundários (ALI et al, 2020;HARAMOTO et al, 2020;RANDAZZO et al, 2020;KUMAR et al, 2021). Embora os processos secundários relatados nos estudos tenham apresentado diferenças operacionais significativas, a implementação de unidades terciárias de tratamento foi fortemente recomendada com o intuito de reduzir a possibilidade de propagação do SARS-CoV-2 através das matrizes aquáticas.…”
Section: Processos Biológicosunclassified
“…Ressalta-se, entretanto, que a eficiência da inativação das partículas virais, incluindo de vírus envelopados como SARS-CoV-2, tem sido influenciada por diversos fatores críticos, como o tempo de contato, dose, pH, temperatura e composição de águas residuais/água (MOHAN et al, 2021), além das condições de manutenção e operação das estações de tratamento (NASSERI et al, 2021). Estudos realizados em plantas de tratamento de esgoto reais no Irã e Israel, por exemplo, indicaram que o processo de terciário de cloração não foi 100% eficaz na remoção de material genético do SARS-CoV-2 das águas residuais em tratamento (ALI et al, 2020;NASSERI et al, 2021).…”
Section: Cloraçãounclassified
See 1 more Smart Citation
“…The Research, Society and Development, v. 10, n. 5, e45910515219, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i5.15219 8 studies have been carried out to determine the efficiency of disinfection systems and foment strategies regarding the adequacy of water and wastewater treatment plants, waste transport and discharge procedures (Cahill & Morris 2020;Zhang et al 2020b;Patel et al 2021). The researches have also aimed to analyze the safety of reused wastewaters in irrigation of food crops, groundwater recharge, cooling industrial processes and recreation porpoises (Ali et al 2020;Bogler et al 2020;Jha et al 2020).…”
Section: Wastewater Surveillance As a Covid-19 Epidemiological Control Approachmentioning
confidence: 99%
“…However, neither study quantified the contribution of identified factors toward the removal of genetic markers. Observations of increased SARS-CoV-2 genetic marker adsorption in thickened primary and waste activated sludge matrices are widely understood (Abu Ali et al, 2021;Aghababaei et al, 2023;Yanaç et al, 2022) to be a primary pathway for virus removal during wastewater treatment. To the best of our knowledge, a long-term study identifying and quantifying the impact of natural decay and fate mechanisms, including adsorption, on the removal of viruses during wastewater treatment has not been conducted or reported in the literature.…”
Section: Introductionmentioning
confidence: 99%